Az egyensúlyi helyzet megbomlása a szerződések jogában: az állam mint szerződő fél - Béky, Ágnes Enikő (Debreceni Jogi Műhely, 2009)
Contractual relations mean balanced cooperation between the parties. Right and obligations on both sides are equal. This seems to be a classic essential of contracts. As of many among the terms and condition in contract law, special situations clam for a different perspective. This essay is about a unique problem in contract law that origins from the ancient dilemma about the role of the state in private law relations.State as a sovereign has original power and hierarchic connection to citizens. In the field of constitutional law, public administration law, criminal law it is necessary to transfer certain right to the state and allow it determining one-sided obligations that cannot be changed in a particular relation. The theory of state immunity failed in the 20th century in private law. Since jurisprudence makes a difference between the role of the state as a merchant and a sovereign, we cannot maintain the old immunity rights of the state anymore.In the essay we examine three specific questions in connection with state participation in contracts. The first part of our study analyzes the strange legal arguments in a famous Hungarian case, called the Subway case. In this case the reasoning of the Supreme Court denied the balanced elements in a private contract and accepted a redefined theory of state immunity in private relations. Although there is a strong political content in the story and right after the criticized decision the Hungarian Civil Code was modified to clear the facts, we want to prove that even today state participation can cause interferences in the coherent theory of contracts.A specific contract type is examined in the second chapter of the essay, the concession agreement. This contract is far from the balanced theory of party positions due to its unique nature and content. We emphasize many different aspects in mixing private and public law nature of provisions and rules. Concession agreement is an excellent example to demonstrate extra-rights on the side of the state.Finally we spare some words on authority contracts in which state authorities can manage debates in public administration procedures with using the private law nature of contracts.